DESIGN & CONSTRUCTION OF OXYGEN SATURATION MEASURING EQUIPMENT THROUGH THE THINGSPEAK SERVER WITH MAX 30100 SENSOR - Winarno Fadjar Bastari; Moch. Arif Anshori; MUHAMMAD RISFAN RAMADHANI (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2022)
The human body requires sufficient oxygen levels for daily life, so it is important for humans to maintain oxygen levels in their bodies. Good oxygen saturation will facilitate the distribution of substances in the body, red blood cells carry oxygen from the lungs and are distributed throughout the body. It is very important for humans to keep oxygen within normal limits. Excess oxygen in the blood or hyperoxaemia: above 120 mmHg. The normal limits for oxygen levels in human blood are between: 75-100 mmHg. Lack of oxygen or hypoxaemia is less than 75 mmHg. A blood oxygen level below 60 mmHg indicates a very severe blood deficiency and you need supplemental oxygen. The design of an oxygen saturation monitoring tool through the Thingspeak server with a max 30100 sensor based on nodemcu 8266 aims to make it easier to monitor oxygen levels in the blood so that it can take early anticipation to avoid unwanted things. The design of this tool is equipped with monitoring using a Thingspeak server that can be connected to the internet or WIFI so that we can do it when we are there. This blood tool is designed using a MAX 30100 sensor as an oxygen detector which is clamped on a finger and then connected to NodeMCU 8266. After waiting for a while the sensor detects oxygen levels < 80% >, 100% NodeMCU 8266 sends data to the LCD and Thingspeak. On the Thingspeak server we can observe the oxygen levels in our bodies. We can use this tool far away so we don't need to go to the hospital or health center to measure the oxygen saturation in our bodies.